STANDAR PROSES PENDIDIKAN JATI DIRI GURU PROFESIONAL - salsabila diva saputri; Adilah Dalimunthe; Astri Marliana Harahap; Indah Prisandra Sianturi (Yayasan Baitul Hikmah al-Zain, 2026)
Education plays an important role in shaping intelligent, character-driven, and adaptive generations in response to the dynamics of modern times. Teachers serve as the main component in ensuring the quality of the learning process through the implementation of educational process standards, which include planning, implementation, and evaluation. This study aims to analyze the implementation of educational process standards, the challenges faced by teachers, and the characteristics of a professional teacher’s identity in the context of modern education. The findings reveal that the implementation of educational process standards in schools is still not optimal due to limited time, facilities, and the lack of continuous training for teachers. Moreover, many teachers face difficulties in adapting to curriculum changes and technological advancements. On the other hand, professional teachers are characterized by strong pedagogical competence, innovative teaching abilities, mastery of educational technology, and integrity with a firm commitment to their profession. With increased professionalism and support from various stakeholders, teachers are expected to become agents of change in creating effective, creative, and relevant learning aligned with the demands of the digital era